Analysis of algorithms and development of the structure of aquaponica control system - Zaloznyi, R. (Energy and Automation, 2025)
The article analyzes the distribution of control tasks in an aquaponic system and presents a three-level aquaponic system control system that combines automatic, automated and manual processes to ensure its efficient and adaptive operation. Based on the mathematical model of the aquaponic system, the analysis of the main control algorithms is carried out: periodic on/off, pulse width modulation (PWM) and P-controller. Their advantages, disadvantages and areas of application are considered. Using the mathematical model of aquaponics, the structure of the control system was created, which made it possible to model and analyze the main control algorithms and, based on it, develop recommendations for choosing a control system algorithm. Based on the modeling results, it was found that none of the considered algorithms provides optimal process parameters, requiring the future development of intelligent aquaponics control algorithms aimed at improving the efficiency of the system and the quality of the final product. Key words: aquaponics, control system, control algorithms, modeling